Access and use of information and communication technology for teaching and learning amongst schools in under resourced communities in the Western Cape, South Africa - Koranteng, Kesewaa (Cape Peninsula University of Technology, 2012)
Thesis (MTech(Information Technology)) --Cape Peninsula University of Technology, 2012 === Due to the legacy of apartheid South Africa is facing developmental discrepancies with inequalities between the advantaged few in the more urban areas and the disadvantaged majority in the rural areas. With quality education being key, not only to the success of an individual but of a country’s development, efforts have been made to ensure equal access for all. ICT is seen as a key enabler to this end. The study investigated the status of ICT deployment and its integration into curricula in schools. The objective was to understand the factors affecting the efforts to achieve successful implementation of ICT integration into schools in underdeveloped areas, to understand the challenges that exist and ultimately, to inform solutions. A qualitative study was conducted, using a case study method. A purposive sampling method was used to select population elements; educators and school coordinators of ICT programs in Western Cape schools (i.e. Kulani Secondary, Sithembele Matiso Secondary, Macassar Secondary and Marvin Park Primary). To gain an understanding of the status quo, literature was explored and semi-structured interviews were conducted with ICT coordinators and educators within the 4 sampled schools. Activity theory was used to provide an analytical framework for the study. Through this framework the aims and objectives of the study were conceptualized and summarized to form a graphical representation of the phenomena under study. In spite of efforts to ensure universal access to ICT, the findings indicate that the status of ICT deployment and its integration into school curricula is far from favourable in underdeveloped schools.